WELLNESS TOURISM IN CHONBURI PROVINCE - Riwatthana, Sisopa; Polngam, Pattaratira; Sriwattanakul, Kumpol (Journal of MCU Nakhondhat, 2023)
This article aims to study the guidelines for the quality development of wellness tourism management. This is a qualitative study by searching for information from documents and research that concern. Analyze data by summarizing and interpreting relevant documents and research that relate and present according to the objectives as follows: 1) Wellness tourism means to travel with purpose and activities to promote or maintain health. Therefore, wellness tourism separates into 2 types comprise health promotion tourism and therapeutic or medical tourism. 2) Factors that support the readiness of wellness tourism in Chonburi Province are the Tourism Policy of Eastern Economic Corridor Planning (EEC). Which focuses on high-income tourists and wellness tourism groups. In addition, found that Chonburi province is well equipped in terms of accommodation with a large number of modern hotels. It is also a province that has many modern health facilities as well. For example, Thammasat Pattaya: The Health and Wellness Innopolis. 3) Wellness tourism activities in Chonburi include Thai Massage, Herbal compress massage, Body scrub activity, Aroma massage, and Hydrotherapy activities. Wellness tourism destinations in Chonburi Province classifies into 3 types include the Thai way of wellness tourism destinations, Natural wellness tourism attractions, and Recreational wellness tourism.